2021
DOI: 10.3390/nano11040846
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Nanoparticles: A Promising Tool to Improve Maize Physiological, Biochemical, and Chemical Traits

Abstract: Lignin, and its derivatives, are the subject of current research for the exciting properties shown by this biomass. Particularly attractive are lignin nanoparticles for their eco- and biocompatibility compared to other nanomaterials. In this context, the effect of nanostructured lignin microparticles (LNP), obtained from alkaline lignin by acid treatment, on maize plants was investigated. To this end, maize seeds were primed with LNP at five concentrations: 80 mg L−1 (T80), 312 mg L−1 (T312), 1250 mg L−1 (T125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…FTIR analysis of LNP, ZnO-NP, and ZnO@LNP was also conducted. The analysis results, reported in Figure 1 b, showed that in the case of LNP, the typical signals of the nanoscaled lignin already observed in previous investigations were found [ 11 ]. In detail, a broad band at 3600–3300 cm −1 , corresponding to hydroxyl groups in phenolic and carboxylic acids and bands around 2936 and 2840 cm −1 , attributed to C-H stretch present in methyl, methylene, and methoxyl groups, were found.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…FTIR analysis of LNP, ZnO-NP, and ZnO@LNP was also conducted. The analysis results, reported in Figure 1 b, showed that in the case of LNP, the typical signals of the nanoscaled lignin already observed in previous investigations were found [ 11 ]. In detail, a broad band at 3600–3300 cm −1 , corresponding to hydroxyl groups in phenolic and carboxylic acids and bands around 2936 and 2840 cm −1 , attributed to C-H stretch present in methyl, methylene, and methoxyl groups, were found.…”
Section: Resultssupporting
confidence: 74%
“…LNP suspension was obtained from alkali lignin by hydrochloric acid treatment. Based on the procedures reported in the literature, 4% ( w / v ) of alkali lignin in ethylene glycol was maintained under stirring for 2 h at 35 °C [ 11 ]. Afterwards, HCl (8 mL, 0.25 M) was mildly added to the solution at a rate of 3–4 drops/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZmmiR528overexpressing transgenic maize plants had reduced lignin content and rind-penetrometer resistance and were prone to lodging under N-luxury conditions [21]. Besides, appropriate dosages of nanostructured lignin microparticles can be used to improve maize seed germination and radicle length [22]. In previous research, we also found several genes involved in cell-wall synthesis and cell elongation under deep sowing, which may also relate to the lignin metabolism [1,4].…”
Section: Discussionmentioning
confidence: 73%
“…They are being extracted from a variety of sources, and large-scale production predominantly arises from the bioethanol and xylose/furfural industries [ 3 , 4 ]. Ironically, around 98% of lignin from the paper and/or pulp industries is being burned, considering it a waste by-product and non-optimized energy resource [ 5 , 6 ]. However, a plethora of applications could be envisioned from lignins, for example, in the synthesis of polymers, dyes and fertilizers, as well as as adhesives in ecological and low-carbon plywood [ 7 ].…”
Section: Introductionmentioning
confidence: 99%